Made wrong, excluded, and ignored: Introduction to a special issue on lesbians and the law. Issue 3 (3rd July 2019) - Dwyer, Angela; Rundle, Olivia
Abstract: For some time now, the specific experiences that lesbians have with the law have been considerably overlooked. This is because there is a focus on how gay males have contact with the law, as gay males are the group whose same-sex intimacies are most often criminalized in legislative frameworks. It is rare for the same-sex intimacies of lesbians to be targeted explicitly in legislative frameworks. This special issue therefore focuses on how lesbians have contact with the law. It features articles focused on what the guest editors conceptualize as how lesbians are being made wrong, being excluded, and being ignored by the law, and each of these are outlined in further detail in this introduction. The articles highlight the relational nexus between lesbians and different frameworks, processes, rules, policies, institutions and applications of law, and the far-reaching impacts this nexus produces in the lives of lesbians around the world.